The Effect of Financial Literacy and Technology Acceptance model on Student Interest in Using Paylater - Nurfaidah; Gazali, Agus Umar; Bunyamin; Rusdiah; Hadidu, Andi; Sudirman (Moneta : Journal of Economics and Finance, 2024)
Globalisation and advancements in information technology have brought about rapid developments in the financial sector, including electronic money that facilitates cashless transactions. One of the latest innovations is SPayLater, an instalment service from Shopee that allows users to make purchases by paying later. Especially among Generation Z students, SPayLater has become a popular choice thanks to its ease of managing monthly budgets with fixed payments. This study adopts an associative approach to explore the impact of financial literacy and technology acceptance model (TAM) on interest in using SPayLater. A survey was conducted among 150 respondents using Google shapes, and the records were analysed using SPSS 25. The results of the t-data analysis show that financial literacy does not have a significant influence on users' interest in using SPayLater, while the variables of the technology acceptance model significantly influence such interest. These findings provide important insights into the factors that drive interest in digital instalment services among university students